ANALISIS PERBANDINGAN RESIKO KONTRAK BIAYA PLUS JASA (Cost Plus Fee Contract) DENGAN KONTRAK LUMPSUM - WINAHYU, FAISAL BUDI (KURVA S JURNAL MAHASISWA, 2015)
In project management will always appear side by side two (2) things are contradictory, namely the opportunity to benefit and the risk of suffering losses, including in the construction services business. Construction activity can be said to be successful if it is able to meet the goal of completion on time is specified, in accordance with the allocated costs and meet quality requirements implied. In a construction project contract type that is often used in construction activities is Lumpsum contract and contract plus service fee (Cost Plus Fee Contract) . Thereby further need to know the level of risk in terms of costs for the use of these two types of contract . For that to know How to analyze Risk Contract Services Cost Plus (Cost Plus Fee Contract) Contract Lumpsum. The method used to analyze the risk of Contract Services Cost Plus (Cost Plus Fee Contract) Contract Lumpsum is using Identify Risks (Risk Identification) is the identification of a process or activity identified cause any risk in the face by an organization . Before analyzed primary data collected beforehand by preparing questionnaires and interviews . Questionnaire respondents using mapping methods with indicators derived from the parameters set out in the contract and the interview techniques used in this study is wawan guided manner in which questions about the material given on the Comparative Study of the respondents to the project with contract Contract Cost Plus Services and Lumpsum. In this analysis can be concluded Risks contract lumsump that the highest risk on indicators 11 and 31 ( PPK obliged to pay to the provider in accordance with the terms of the contract and inspection of the work , including checklist on the handover of the first and handover Thank II ) against the nine respondents out of 30 respondents the risk value of 2% , the risk was worth the risk of 11 % , and a small risk with the risk value 87 % . While the risk of plus service contract costs ( cost plus fee contract) is the highest risk indicator 1,3,5,6,7,8 and 10 to 8 respondents from 30 respondents with a value of 4 % due to the risk of this type of 2 contract which does not use SPMK SPMK is a follow- on issuance and payment is only appropriate SPK mail order so risky work is not appropriate and could be risky payment increases / decreases , risk was worth the risk of 17 % , and a small risk with the risk value 79 %